Berbagi Pengalaman Bersama Masyarakat Buton pada Pesta Adat Tahunan di Desa Kondowa Dongkala Kec. Pasarwajo Kab. Buton - Laxmi Laxmi; Nasruddin Suyuti; Ashmarita Ashmarita; Raemon Raemon; Hidayah Rahman (Jurnal Kabar Masyarakat, 2023)
The implementation of a traditional party once a year makes the people of Kondowa Dongkala Village very attentive and collaborate in preparing everything related to the village party, where in the annual party there are things called pikolambu and kabaria. The implementation of this annual traditional party has the meaning of expressing gratitude for the blessings, gifts and long life given to the people of Kondowa Dongkala village, which means giving thanks to Allah SWT because one year the people of Kondowa Dongkala always stand together, sit together for the good fortune the bring. God has given it to the people of Kondowa Dongkala Village.